A conceptual model of the role of the instructor in fostering students’ mathematical creativity - Yaftian, Narges (Lembaga Pengembangan Publikasi Ilmiah dan Buku Ajar, Universitas Muhammadiyah Surakarta, 2023)
Several studies tried to introduce some of the efficient factors that can influence fostering mathematical creativity in learning environments. since some of the variables associated with mathematical creativity in educational environments depend on the culture, conducting research in this area seems necessary. It should be noted that the contribution of Iranian researchers to these studies is very small. The paper aims to study the role of instructors in nurturing creativity in mathematics students from math students’ point of view and to present a conceptual model. The research is a qualitative study conducted using grounded theory. Participants were selected from university students who are studying mathematics in the universities of the city of Tehran in Iran using purposive sampling and the sampling is stopped until theoretical saturation. Finally, semi-structured in-depth interviews were conducted with 10 students. Interviews were audiotaped, transcribed, and coded in the two stages of free coding and axial coding. Classification of codes led to numerous categories. The findings show that instructors can influence several aspects: belief, intention, mathematical knowledge, mathematical thinking, and personality characteristics such that being persistent, being a risk taker, and forgetting fixation.